FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PEMUPUKAN KELAPA SAWIT DI PT. WIRA INOVA NUSANTARA DESA SUSUK DALAM KECAMATAN SANDARAN KABUPATEN KUTAI TIMUR PROVINSI KALIMANTAN TIMUR - Gilas Arianto; Mujibu Rahman; Jamaluddin (JURNAL AGRIMENT, 2020)
This research is motivated by the importance of fertilization in order to increase sufficient nutrients, promote healthy plant growth and maximum production of Fresh Fruit Bunches and increase resistance to pests and diseases. This is what encourages researchers to analyze what factors affect the work productivity of oil palm fertilizing employees. Therefore, the purpose of this study is to analyze the factors of age, years of service, and education on the work productivity of fertilizing employees. Collecting data in this study is by giving questionnaires and interviews to the respondents. The independent variables in this study are Age (X1), Working Period (X2), and Education (X3) and the Bound Variable is Productivity (Y). To determine the effect of independent variables on dependent variables, researchers used the multiple linear regression method. From the t test results indicate that the labor productivity of fertilizing employees at PT. Wira Inova Nusantara was significantly influenced by tenure factors, while age and education did not have a significant effect on labor productivity of fertilizing employees at PT. Wira Inova Nusantara.